'Being able to take that mask off': adolescent clients' experiences of power in person-centered therapy relationships. (2nd April 2020) - Cook, David; Monk, Laura
ABSTRACT: Person-centered therapy aims to help clients actualize their own power. When working with adolescents, the developmental needs of the client and the power difference between client and therapist may present additional barriers to this. This study sought to understand the power dynamics of the therapy relationship from the adolescent client's perspective. Seven adolescent clients in person-centered therapy took part in semi-structured interviews. Interpretative phenomenological analysis was used to explore the meaning they made of their experiences. Participants' experiences centered around five themes: 1) feeling my vulnerability entering a relationship with a powerful figure; 2) being invited to express myself; 3) evaluating if I can trust my counselor; 4) feeling I'm in control in a relationship with boundaries; and 5) exercising my power in the relationship. Participants described a process whereby, helped by their counselor, they negotiated an unequal power dynamic and were able to exercise power in the relationship. Implications for person-centered therapists working with adolescents are considered.